A Review of Customer Churn Prediction Related Issues Using Data Mining Methods - Venkatesh, S; Jeyakarthic, M (International Journal of Computer Sciences and Engineering, 2025)
Customer churn prediction is a challenging target but a very necessary and essential in emerging serviceoriented businesses. It is also one of the important issues in customer relationship management. To predict a customer there is a number of data mining techniques applied for churn prediction, this paper reviews some recent developments and compares them in terms of data pre-processing and prediction techniques